Procli In Platonis Parmenidem Commentaria III. - Steel, Carlos (Scriptorum classicorum bibliotheca Oxoniensis., 2009)
The Commentary on Plato's Parmenides by Proclus (AD 412-85) is the most important extant document on the interpretation of this enigmatic dialogue, and has had a crucial influence on all subsequent readings. In Proclus' Commentary, the Parmenides provides the argumentative and conceptual framework for a scientific theology wherein all mythological discourse about the gods can be integrated. Its exposition was therefore the culmination of the curriculum of the Platonicschool. This theological reading of the Parmenides persisted, through the medium of Ficino, until the nineteenth century. Previo.